The Correlation between Demographical and Lifestyle Factors and Traditional Chinese Medicine Constitution among Macau Elderly Individuals. (19th April 2021) - Bai, Qian; Chuang, Yaochen; Zhao, Yonghua; Wang, Yao; Ge, Pu; Xu, Youhua; Bian, Ying
Abstract : Objectives . To measure the distributed characteristics of Traditional Chinese Medicine (TCM) constitutions, as well as related factors with biased TCM constitutions among the elderly individuals in Macau. Methods . The elderly individuals from elderly healthcare centers located in Macao Peninsula, Taipa, and Coloane were selected as research samples. The basic information questionnaire and the Constitution in Chinese Medicine Questionnaire (CCMQ) for elderly were employed. Descriptive analysis was applied to illustrate demographical characteristics and TCM constitution distribution. Exploratory factor analysis (EFA) was conducted to explore potential factors influencing biased constitutions, and weight of each variable for constitution was further calculated. Results . A total of 313 participants were recruited. Eighty-six (27.48%) elderly were identified as balanced constitution; others were biased constitutions accounting for 72.52%. Distribution differences related to gender and age were identified among participants with unbalanced constitutions. Four biased constitutions were further analyzed with EFA. For qi-stagnation and yang-deficiency constitutions, three similar factors were determined in the domains of education, sleeping habits, and lifestyle behaviors, successively. Although four factors were identified in phlegm-dampness constitution, the latter two belonged to lifestyle behaviors and the former two were education and sleeping habits. For yin-deficiency constitution, education, tobacco-alcohol consumption, sleeping habits, and exercise were four dimensions of potential influential factors. Tobacco consumption, sleep, and exercise duration weighted the most for qi-stagnation constitution; sleep duration, education level, and sugar-containing beverage intake for phlegm-dampness; length of education, alcohol consumption, and education level for yang-deficiency constitution; and weekly exercise hours, sleep duration, and education level for yin-deficiency constitution. Conclusion . The prevalence rate of biased constitutions was relatively high among elderly residents in Macau. Relations between demographical and lifestyle behavioral factors and biased constitutions were identified in this study. Controlling these influential factors might be beneficial for health management of Macau elderly individuals.